2009
DOI: 10.1001/archdermatol.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil as Therapy for Pyoderma Gangrenosum

Abstract: Background: Pyoderma gangrenosum is an ulcerative condition that may be associated with inflammatory bowel disease or inflammatory arthritis. In addition to local wound care, management often includes the use of systemic corticosteroids or systemically administered immunomodulatory agents. Observations: We retrospectively analyzed 7 patients with pyoderma gangrenosum who were treated with mycophenolate mofetil. Patients were included if they had a diagnosis of pyoderma gangrenosum and were treated with mycophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
1
27
0
2
Order By: Relevance
“…This is consistent with the upper limit of previously reported response rates of 57% to 86%. Our patients responded to doses ranging from 1 to 3 g total daily, and previous reports have described doses from 1 to 4 g total daily, 1,[9][10][11][12] suggesting that requirements vary substantially. The 4 patients in our series who showed no clear response received 1, 2, 4, and 12 months of MMF, respectively.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is consistent with the upper limit of previously reported response rates of 57% to 86%. Our patients responded to doses ranging from 1 to 3 g total daily, and previous reports have described doses from 1 to 4 g total daily, 1,[9][10][11][12] suggesting that requirements vary substantially. The 4 patients in our series who showed no clear response received 1, 2, 4, and 12 months of MMF, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…13 In the PG literature, MMF has been used alone, together with prednisolone and in combination with other steroid-sparing agents. 1,9,10 In our series, many patients had combination therapy, generally with cyclosporine. Seven patients took a single additional steroid-sparing agent, 6 patients took 2, and 2 patients required a cocktail of 3 or more additional agents, reinforcing again the need for individualized treatment regimens.…”
Section: Discussionmentioning
confidence: 77%
“…Cyclosporin, azathioprine, dapsone, clofazimine, thalidomide and mofetil mycophenolate have also been used. 9 Recently, infliximab was used as an alternative treatment for PG. 10 In 2004, Su et al 11 proposed a set of primary and secondary diagnostic criteria for PG.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of MMF in PG showed over half of patients gain complete ulcer resolution. 1 Pyoderma gangrenosum with oral involvement is rare. There have been a handful of case reports in the literature linking oral PG with inflammatory bowel disease and hematological disorders.…”
Section: Figurementioning
confidence: 99%